My family history - O'Connor, Jane (O'Connor, Jane. Fancy Nancy., 2010)
Nancy writes a report for school about her great-grandfather, making things up so he seems less ordinary, but when she learns that Grandpa will be there to hear her read the report aloud she realizes she was dishonest.